2012
DOI: 10.1158/0008-5472.can-11-4061
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Raman Spectroscopy for In Vivo Skin Cancer Diagnosis

Abstract: Raman spectroscopy is a noninvasive optical technique capable of measuring vibrational modes of biomolecules within viable tissues. In this study, we evaluated the application of an integrated real-time system of Raman spectroscopy for in vivo skin cancer diagnosis. Benign and malignant skin lesions (n ¼ 518) from 453 patients were measured within 1 second each, including melanomas, basal cell carcinomas, squamous cell carcinomas, actinic keratoses, atypical nevi, melanocytic nevi, blue nevi, and seborrheic ke… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
339
6
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(361 citation statements)
references
References 40 publications
11
339
6
5
Order By: Relevance
“…These biopsy procedures are invasive, inefficient, and inconvenient. More importantly, the process has low diagnostic accuracy (49-81% among dermatologists for melanoma, the most deadly form [2]). The number of pigmented lesions needed to be excised to identify one melanoma ranges from 22 to 59 for experienced versus new general practitioners [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These biopsy procedures are invasive, inefficient, and inconvenient. More importantly, the process has low diagnostic accuracy (49-81% among dermatologists for melanoma, the most deadly form [2]). The number of pigmented lesions needed to be excised to identify one melanoma ranges from 22 to 59 for experienced versus new general practitioners [3].…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in near-infrared lasers, optical filters, fiber optics and CCD cameras have greatly improved its sensitivity in detecting the chemical composition of biological tissues. In the most recent decade, the Raman optical fiber probe has allowed for fast and accurate cancer diagnostics, including ex vivo study of breast [4,5], prostate [6], lung [7] and skin [8,9], and in vivo study of breast [10], cervical [11], and skin [2,12]. Recent clinical studies from our group [12] and others [2] have demonstrated that RS has high diagnostic accuracy in discriminating skin melanoma from nonmelanoma pigmented lesions.…”
Section: Introductionmentioning
confidence: 99%
“…2012; Lui et al . 2012). By coupling a Raman system to a microscope set‐up, one can achieve submicrometre spatial resolutions (Maier & Treado 2004).…”
mentioning
confidence: 99%
“…65 More recently, Lui et al developed an optimised hand-help Raman probe that allowed real-time (less than 1 second) in-vivo diagnostic. 66 This large study (more than 1000 cases of skin cancers and other skin diseases) showed that it is possible to distinguish malignant and premalignant from benign lesions, melanomas from benign pigmented skin lesions, and melanomas from seborrheic keratoses, with sensitivities between 95% and 99%, although specificities range between 15% and 54%. 66 In 1998, Mahadevan-Jansen et al published in vivo results using a fibre-optic Raman probe to analyse dysplastic change in cervical tissue.…”
Section: Intra-operative Surgical Applicationsmentioning
confidence: 99%
“…66 This large study (more than 1000 cases of skin cancers and other skin diseases) showed that it is possible to distinguish malignant and premalignant from benign lesions, melanomas from benign pigmented skin lesions, and melanomas from seborrheic keratoses, with sensitivities between 95% and 99%, although specificities range between 15% and 54%. 66 In 1998, Mahadevan-Jansen et al published in vivo results using a fibre-optic Raman probe to analyse dysplastic change in cervical tissue. 23 Silica-silica fibres were shown to cause less signal disruption than sapphire and liquid guide fibres despite their tendency to generate significant background signal at low wavenumbers (below 900 cm -1 ).…”
Section: Intra-operative Surgical Applicationsmentioning
confidence: 99%